Implementation Of The Education Management Information System [EMIS] At The IMMIM Putra Makassar Islamic Boarding School - Julian ana (Universitas Islam Negeri Alauddin Makassar, 2023)
This research is motivated by the importance of EMIS data input for Islamic education institutions under the auspices of the Ministry of Religion, namely as a forum for administrative convenience, channeling assistance, as well as supporting planning and policy-making activities for Islamic education programs at the Ministry of Religion. The purpose of this study was to obtain an overview and analyze the application of EMIS at the IMMIM Putra Makassar Islamic Boarding School. To obtain an overview and analyze the supporting and inhibiting factors for implementing EMIS at the IMMIM Putra Makassar Islamic Boarding School. This type of qualitative descriptive research used in this study is intended to analyze the application of the Education Management Information System (EMIS) at the IMMIM Putra Makassar Islamic Boarding School. The sample in this study was the EMIS Data Manager. The data collection techniques used were the interview method, the observation method, and the documentation method. The data analysis technique used is Data Collection, Data Reduction, Data Display and Conclusion Drawing and Verification. From the results of the research the role of the leadership is quite good in every Modern Islamic Boarding School for Al-Quran Education IMMIM Makassar which is one of the organizational units because humans are the most important element. For this reason, it can be said that the role of the leader in implementing EMIS is quite good, the ability of the leader to foster a climate of cooperation easily and can mobilize existing resources so that they can utilize them and can run effectively and efficiently.